(untitled) (Eurasian Journal of Learning and Academic Teaching, 2022)
Since the content of education is connected with life, modern science, the tasks are to accelerate the economic development of the country, to improve the quality of education and the organization of education through the use of multimedia, automation of production, intensification on the basis of computerization. ’z finds the opposite